Drain Back Systems in Laboratory and in Practice. (May 2015) - Perers, Bengt; Furbo, Simon; Fan, Jianhua; Kong, Weigang; Chen, Ziqian
Abstract: Drain Back systems with ETC collectors are tested and analyzed in a Danish - Chinese cooperation project. Experiences from early work at DTU, with drain back, low flow systems, was used to design two systems: 1) One laboratory system at DTU. 2) One demonstration system in a single family house in Sorö Denmark. Detailed monitoring and modelling/validation of the system in the DTU lab is done, to be able to generalize the results, to other climates and loads by simulation and to make design optimizations. The advantage with drain back, low flow systems, is that the system can be made more simple with less components and that the performance can be enhanced. Also problems with long term degradation of glycol collector loops are totally avoided. A combination of the drain back and system expansion vessel was tested successfully. It is very important to achieve a continuous slope for the pipes in the collector loop to have a safe reliable operation. The components should also be designed and marked so that only one correct mounting option is possible, like forward and return pipes to/from the collector of slightly different sizes or color. Adapted installer education and training is a very important step to have success with drain back systems. Practices used in glycol systems may give serious failures.